The Effect of Leadership Styles of Principals, Personality and Work Motivation on the Performance of Elementary School Teachers in Sekolah Alam - Wibowo, Agung; Indupurnahayu, Indupurnahayu; Avessina, Mohammad Jibriel (prodima@fe.uika-bogor.ac.id, 2025)
The quality of education is one of the main pillars in the development of human resources which is very important for national development. Quality education can be realized, one of which is through the performance of good educators. This study aims to analyze the influence of the principal's leadership style, teacher personality, and teacher personality on the performance of elementary school teachers in natural schools. The primary data in this study were obtained from questionnaires distributed to 55 elementary school teachers at Sekolah Alam and then statistically analyzed using the Multiple Linear Regression Analysis method using data processing tools, namely Microsoft Excel and SPSS. The results of the analysis showed that there was a positive influence on the leadership style of the principal. schools, personality and work motivation of teachers on the performance of elementary school teachers. The functional relationship in the form of the regression equation is Y = 8.053 + 0.081X1 + 0.420X2 + 0.226X3. The Teacher Personality Variable has the greatest influence where each increase in the Personality variable will increase the Teacher Performance Variable by 0.420 units.